Keefektivan Konseling Kelompok Teknik Spirituality Cognitive Restructuring untuk Meningkatkan Self Esteem Siswa - Faith, Dwi Bhakti Indri M (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2016)
This study aimed to test the effectiveness of group counseling with spirituality-cognitive restructuring technique to improve studentsâ self esteem. This was an experimental study with pretest-posttest control group design. There were two groups assigned through purposive sampling based on the result of pre-test conducted by the researcher. The data analysis technique of this study was Wilcoxon Signed-rank-test. The result of Wilcoxon test showed that asymp.sig (2-tailed) was 0.026 < 0.05, so Ha was accepted and Ho was rejected on the experimental group. In other words, group counseling with spirituality-cognitive restructuring technique was effective to Improve Studentsâ self esteem. This study could be a guideline for the counselor in implementing Group counseling with spirituality-cognitive restructuring technique to improve the studentsâ self esteem. The future researcher is expected to be able to implement this integrative approach in a broader area.